2009 IEEE MTT-S International Microwave Symposium Digest 2009
DOI: 10.1109/mwsym.2009.5165908
|View full text |Cite
|
Sign up to set email alerts
|

A capacitively-loaded MEMS Slot element for wireless temperature sensing of up to 300°C

Abstract: In this paper we present a new slot antenna with an embedded temperature sensor for remote sensing in harsh environment applications. When the antenna is illuminated with a plane wave it returns a signal. The returned signal's frequency is modulated by the loaded capacitance formed by an array of MEMS bimorph (metal-dielectric) cantilevers. The MEMS cantilevers deflect downwards when the temperature is changed from 20q qC to 300qC. As a result, the resonant frequency of the slot is linearly tuned from 19.45 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…The Haiying Huang research team reported the microstrip patch antenna temperature sensor, based on Rogers materials, reaching a maximum temperature of 280 °C, beyond which the high-temperature application capacity is still needed [ 29 , 30 , 31 ]. The Ahsan Choudhuri research team presented a concept and model of a passive wireless temperature sensor based on metamaterial for harsh-environment applications, but no measurement experiments [ 32 ].The measuring range of a temperature sensor developed at Purdue University, which is based on microelectromechanical systems technology, reached only 300 °C [ 33 ]. Slotted wireless passive temperature sensors were fabricated by Wu et al [ 34 ] and Cheng et al [ 35 ], but they are not reliable and durable because the metal coating on side walls are difficult to process and easily fall off.…”
Section: Introductionmentioning
confidence: 99%
“…The Haiying Huang research team reported the microstrip patch antenna temperature sensor, based on Rogers materials, reaching a maximum temperature of 280 °C, beyond which the high-temperature application capacity is still needed [ 29 , 30 , 31 ]. The Ahsan Choudhuri research team presented a concept and model of a passive wireless temperature sensor based on metamaterial for harsh-environment applications, but no measurement experiments [ 32 ].The measuring range of a temperature sensor developed at Purdue University, which is based on microelectromechanical systems technology, reached only 300 °C [ 33 ]. Slotted wireless passive temperature sensors were fabricated by Wu et al [ 34 ] and Cheng et al [ 35 ], but they are not reliable and durable because the metal coating on side walls are difficult to process and easily fall off.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches were made to develop a passive, wireless temperature sensor for high temperature operations. Scott and Peroulis [8] presented a slot antenna with an embedded temperature sensor which can sense up to 300°C. Yang [9] proposed a silicon carbide wireless sensing system that can operate at 450°C under high centrifugal load.…”
Section: Introductionmentioning
confidence: 99%
“…For temperature sensors, two main principles based on the variability of the RF resonance have been studied: modification of electromagnetic coupling by bimorph cantilever [1][2][3] and variation of the substrate permittivity [4][5]. The second principle is especially interesting as its fabrication is very simple (only metal patterning on substrate is required).…”
Section: Introductionmentioning
confidence: 99%